REFLECTION ON THE MOTIVES OF HIJRAN AND SEPARATION IN THE INTERPRETATION OF WOMAN’S PSYCHOLOGY (IN THE EXAMPLE OF THE CREATION OF ZEBO MIRZO) (TAMADDUN NURI JURNALI, 2025)
In this article, the use of motives of emigration and separation in modern Uzbek poetry to illuminate the expression of the female psyche is interpreted on the example of the work of the famous poetess Zebo Mirzo.